Evaluation of Pomegranate Peel Powder and Pseudomonas Fluorescens Against Pythium Aphanidermatum The Causal Agentof Cucumber Seedling Damping-Off - Saleh, Nahida; Al-Juboory, Saba (Iraqi Journal of Science, 2023)
This study was conducted to evaluate the activity of pomegranate (Punica granatum L.) peel powder and Pseudomonas fluorescens against Pythium aphanidermatum the causal agent of cucumber seedlings damping-off. Results showed that augmenting of pomegranate peel powder at 2%, P. fluorescens suspension contain 4×107cfu/ml, and the fungicide Previcure N at 0.5 ml/L to culture media (PDA) were inhibited the pathogen growth by 100, 100 and 72.1% respectively. Results of greenhouse experiment indicated that treatment of cucumber seeds with pomegranate peel powder, reduced pre-emergence damping-off percentage to 3.3% compared with 16.6% disease with P. fluorescens and 96.6% in control treatment (pathogen only). No significant differences were observed between fungicide and pomegranate peel powder (p=0.05), while the fungicide was more active than the bacteria in reducing pre-emergence damping-off percentage. Pre-emergence and post-emergence damping-off of seedlings reduced by both pomegranate peel powder and the bacteria compared with control (pathogen only). P.fluorescens increased fresh and dry weights and plant heights, while pomegranate peel powder didn’t affect these growth parameters.